Operando Structure-Activity-Stability Relationship of Iridium Oxides during the Oxygen Evolution Reaction - Mom, Rik V.; Falling, Lorenz J.; Kasian, Olga; Algara-Siller, Gerardo; Teschner, Detre; Crabtree, Robert H.; Knop-Gericke, Axel; Mayrhofer, Karl J.J.; Velasco-Vélez, Juan Jesús; Jones, Travis E. (ACS Catalysis, 2022)
Creating active and stable electrodes is an essential step toward efficient and durable electrolyzers. To achieve this goal, understanding what aspects of the electrode structure dictate activity and catalyst dissolution is key. Here, we investigate these aspects by studying trends in the activity, stability, and operando structure of iridium oxides during the oxygen evolution reaction. Using operando X-ray photoelectron and X-ray absorption spectroscopy, we determined the near-surface structure of oxides ranging from amorphous to crystalline during the reaction. We show that applying oxygen evolution potentials universally yields deprotonated μ2-O moieties and a μ1-O/μ1-OH mixture, with universal deprotonation energetics but in different amounts. This quantitative difference mainly results from variations in deprotonation depth: surface deprotonation for crystalline IrO2 versus near-surface deprotonation for semicrystalline and amorphous IrOx. We argue that both surface deprotonation and subsurface deprotonation modify the barrier for the oxygen evolution and Ir dissolution reactions, thus playing an important role in catalyst performance.
CRIS-Team Scopus Importer:2022-05-06
Keywords: electrocatalysis; electrolysis; iridium oxide; operando spectroscopy; oxygen evolution reaction; X-ray absorption spectroscopy